Penerapan Media Video Youtube Pada Pembelajaran Nilai-Nilai Kehidupan dalam Teks Hikayat Kelas X - Aini, Miladia Nur; Septiana, Ika; Pudjowati, Anis Tri (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2024)
The use of YouTube as a learning tool Indonesian Is a method that can be adopted by educators to develop technology learning. This research aims to illustrate the application of YouTube video media to learning life values in class X saga texts. This type of research is mixed. Data were collected through test and non-test methods (such as observation and documentation). Data analysis is done through triangulation techniques. This research uses descriptive-qualitative research methods. Researchers have used the YouTube platform in the process of learning Indonesian material in class X at SMA Negeri 14 Semarang. Teachers can develop technology-based learning by utilizing YouTube as a learning tool for Indonesian subjects. YouTube media can be used and accessed by everyone, including students. Researchers have used YouTube media used in the learning process of Indonesian class X. According to the results of test and non-test data analysis, it can be concluded that youtube video media can be applied to learning saga texts in grade X students.